2022
DOI: 10.1017/s136898002200043x
|View full text |Cite
|
Sign up to set email alerts
|

Personal motivation, self-regulation barriers and strategies for weight loss in people with overweight and obesity: a thematic framework analysis

Abstract: Objective: To explore motivations, self-regulation barriers, and strategies in a multi-ethnic Southeast Asian population with overweight and obesity. Design: Qualitative design using semi-structured face-to-face and videoconferencing interviews. Data was analyzed using thematic framework analysis and constant comparison method. Setting: Specialist weight management clinic. Participants: 22 participants were purposively sampled from 13 April to 30 April… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 42 publications
(55 reference statements)
1
15
0
Order By: Relevance
“…As weight management is an integral aspect of population health, we should not be typecasting or identifying people with overweight and obesity for weight management but empowering people with the skills and resources to manage their weight independently. This is especially because of the global weight gain observed during the COVID-19 pandemic [ 47 ], which could be associated with varying levels of personal motivation [ 5 ], peer influence [ 48 ], and self-regulation [ 49 ]. Although many purchased home gym equipment during this period, the sustained use of such equipment without peer influence or health coaching may not have been high.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As weight management is an integral aspect of population health, we should not be typecasting or identifying people with overweight and obesity for weight management but empowering people with the skills and resources to manage their weight independently. This is especially because of the global weight gain observed during the COVID-19 pandemic [ 47 ], which could be associated with varying levels of personal motivation [ 5 ], peer influence [ 48 ], and self-regulation [ 49 ]. Although many purchased home gym equipment during this period, the sustained use of such equipment without peer influence or health coaching may not have been high.…”
Section: Discussionmentioning
confidence: 99%
“…A weight reduction of 5%-10% has been shown to lower the risk of cardiometabolic diseases by improving cardiometabolic measures such as high waist circumference, high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), high blood glucose level, and high blood pressure [ 4 ]. However, weight loss through behavioral modification remains challenging because of the lack of self-regulation and motivation [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…While typical weight management programs behaviour have been effective in promoting weight loss through caloric restrictions and increased physical activity (Gudzune et al., 2015), participants of such programs were shown to regain more than 80% of the weight lost within 5 years (Anderson et al., 2001). Such weight cycling has been associated with covert behavioural factors such as emotional eating (Braden et al., 2016; Chew et al., 2022), a behaviour that is commonly unaddressed in conventional weight‐loss programmes.…”
Section: Introductionmentioning
confidence: 99%
“…Although one study reported improved outcomes when health coaching was used in addition to a smartphone app, the sample in each group was small, undermining the study’s reliability [ 46 , 47 ]. Interventional effects may also be influenced by personal intention, motivation [ 48 ], socioenvironmental resources, and interventional engagement for weight loss [ 49 ]. We also found intraprogram variations in health-coaching programs.…”
Section: Discussionmentioning
confidence: 99%